Leading in times of crisis and remote work: perceived consideration leadership behavior and its effect on follower work engagement - Sedefoglu, Didem; Ohly, Sandra; Schmitt, Antje; Göritz, Anja S. (Frontiers in Organizational Psychology, 2024)
Based on the job-demands resources theory, we examine whether leadership behavior affects followers' work engagement in the context of remote work during times of crisis, and how this effect can be explained. We focus on consideration leadership and its impact on followers' engagement under conditions of enforced remote work during the COVID-19 pandemic. Therein, we examine the role of optimism as a potential mediator. To better understand how the impact of consideration leadership behavior unfolds during crises, we examine whether being new to remote work and feeling personally impacted by COVID-19 amplified the proposed relationship between consideration leadership and followers' engagement. A sample of 729 German employees participated in a threewave study across six weeks in May and June 2020. Longitudinal structural equation modeling uncovered direct positive effects of consideration leadership on changes in followers' work engagement in the second time lag (T2 to T3), while optimism did not mediate this effect. Multigroup comparisons revealed that employees who worked from home were particularly responsive to consideration leadership. No moderating effects were found for whether the COVID-19 pandemic personally impacted employees. The discussion highlights the critical role of leadership in followers' motivation and well-being in times of crisis and remote work.